Association of First-Line and Second-Line Antiretroviral Therapy Adherence. (9th September 2014) - Ramadhani, Habib O.; Bartlett, John A.; Thielman, Nathan M.; Pence, Brian W.; Kimani, Stephen M.; Maro, Venance P.; Mwako, Mtumwa S.; Masaki, Lazaro J.; Mmbando, Calvin E.; Minja, Mary G.; Lirhunde, Eileen S.; Miller, William C.
Abstract : Adherence to first-line ART is an important predictor of adherence to second-line ART. Improving adherence prior to switch is critical to improve patient outcomes. Abstract : Background.  Adherence to first-line antiretroviral therapy (ART) may be an important indicator of adherence to second-line ART. Evaluating this relationship may be critical to identify patients at high risk for second-line failure, thereby exhausting their treatment options, and to intervene and improve patient outcomes. Methods.  Adolescents and adults ( n = 436) receiving second-line ART were administered standardized questionnaires that captured demographic characteristics and assessed adherence. Optimal and suboptimal cumulative adherence were defined as percentage adherence of ≥90% and <90%, respectively. Bivariable and multivariable binomial regression models were used to assess the prevalence of suboptimal adherence percentage by preswitch adherence status. Results.  A total of 134 of 436 (30.7%) participants reported suboptimal adherence to second-line ART. Among 322 participants who had suboptimal adherence to first-line ART, 117 (36.3%) had suboptimal adherence to second-line ART compared with 17 of 114 (14.9%) who had optimal adherence to first-line ART. Participants who had suboptimal adherence to first-line ART were more likely to have suboptimal adherence to second-line ART (adjusted prevalence ratio, 2.4; 95% confidence interval, 1.5–3.9). Conclusions.  Adherence to first-line ART is an important predictor of adherence to second-line ART. Targeted interventions should be evaluated in patients with suboptimal adherence before switching into second-line therapy to improve their outcomes.